A thymosin repeated protein1 reduces white spot syndrome virus replication in red claw crayfish Cherax quadricarinatus. (July 2018) - Li, Dong-li; Chang, Xue-jiao; Xie, Xiao-lu; Zheng, Shu-cheng; Zhang, Qiu-xia; Jia, Shu-ao; Wang, Ke-jian; Liu, Hai-peng
Abstract: The β-thymosins are a group of structurally related, highly conserved intracellular small peptides in vertebrates with various biological functions, including cytoskeletal remodeling, neuronal development, cell migration, cell survival, tissue repair and inhibition of inflammation. In contrast to vertebrates, the function of β-thymosin is not fully understood in crustaceans. Previously, we found that a thymosin-repeated protein1 ( CqTRP1 ) gene was up-regulated after white spot syndrome virus (WSSV) challenge in hematopoietic tissue (Hpt) cells from the red claw crayfish Cherax quadricarinatus . To further identify the effect of CqTRP1 on WSSV infection, a full length cDNA sequence of β-thymosin homologue was cloned and analyzed from red claw crayfish followed by functional study. The CqTRP1 cDNA contains an open reading frame of 387 nucleotides encoding a protein of 129 amino acids with a putative molecular mass of 14.3 kDa. The amino acid sequence showed high identity with other β-thymosins and contained three characteristic thymosin β actin-binding motifs, suggesting that CqTRP1 was a member of the β-thymosin family. Tissue distribution analysis revealed a ubiquitous presence of CqTRP1 in all the examined tissues with the highest expression in hemocytes, Hpt and gonad at the transcriptional level. Interestingly, the gene silencing of endogenous CqTRP1 by RNAi enhanced the WSSV replication in Hpt cells. Meanwhile, the WSSV replication was significantly reduced in the Hpt cell cultures if overloaded with a recombinant CqTRP1. Taken together, these data clearly indicated that CqTRP1 was likely to be associated with the anti-WSSV response in a crustacean C. quadricarinatus, which provides new strategy against white spot disease in crustacean aquaculture. Highlights: CqTRP1 was a member of the β-thymosin family and expressed widely in various tissues of red claw crayfish. Gene silencing of endogenous CqTRP1 enhanced the WSSV replication in red claw crayfish Hpt cells. Overloading of recombinant CqTRP1 inhibited the replication of WSSV in red claw crayfish Hpt cells.